Phonetic Sound Alignment of Indonesian Betawi Dialect with Korean Hangeul Characters Representation - Thoriq, Abriel (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
The successful adaptation of the Hangeul characters to the Cia – cia local language in Southeast Sulawesi is one clear example of how a foreign writing system can be used to phonetically document a local language. This case shows that Hangeul has the flexibility to represent the sounds of local languages that do not yet have their own script system. Similarly, the Betawi dialect of Indonesian, which has distinctive phonetic features, has yet to be documented with an appropriate writing system. This lack of documentation is a challenge in regional language preservation efforts. Based on this background, this study aims to examine the sound harmony of the Betawi dialect using the Korea Hangeul characters as an alternative writing system. This research uses articulatory phonetic theory with descriptive qualitative method. Data were collected through observation and documentation of the types of phonemes and clusters in the Betawi dialect. The analysis involved transcribing the data into the IPA to describe each sound in detail, followed by matching them with Hangeul Characters based on similarities in place and manner of articulation. The results show that most Betawi dialect sounds can be accurately, although some complex phonemes and consonant clusters require special representational approaches. This study concludes that Hangeul holds significant potential as an alternative writing system for the modern and sustainable preservation of the Betawi dialect.